Bidirectional Power Flow Control in AC/DC Hybrid System under AC and DC Fault Conditions - Wai Wai Hnin; Zarchi Linn; Soe Win (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
This paper presents a hybrid AC-DC microgrid to reduce the process of multiple conversions in an individual AC microgrid or DC microgrid. The proposed hybrid microgrid compose of both AC microgrid and DC microgrid connected together by bidirectional interlink converter (BIC). Utility grid, 150kVA diesel generator (DG) and 100kW AC load are connected in AC microgrid. DC microgrid is composed of 100 kW photovoltaic array (PV), 20kW battery energy storage system (BESS) and 20kW DC load. The droop control technique is applied to control the system for power sharing within the sources in AC/DC hybrid microgrid in proportion to the power rating. When the faults occur at AC bus, protection signal applied to breaker for isolating the healthy and faults system. DC faults occur at DC bus, DC breaker isolate the AC and DC bus. The system performance for power flow sharing on hybrid AC-DC microgrid is demonstrated by using MATLAB/SIMULINK.Keywords: AC fault, DC fault, droop control, hybrid microgrid, power flow.